Identification by FFPE RNA‐Seq of a new recurrent inversion leading to RBM10‐TFE3 fusion in renal cell carcinoma with subtle TFE3 break‐apart FISH pattern. Issue 6 (7th April 2016) - Just, Pierre‐Alexandre; Letourneur, Franck; Pouliquen, Christelle; Dome, Florence; Audebourg, Anne; Biquet, Philippe; Vidaud, Michel; Terris, Benoit; Sibony, Mathilde; Pasmant, Eric
Abstract : Gene fusions involving TFE3 defines the "Xp11.2 translocations" subclass of renal cell carcinomas (RCCs) belonging to the MiT family translocation RCC. Four recurrent TFE3 fusion partners were identified to date: PRCC, ASPSCR1, SFPQ, and NONO . Break‐apart TFE3 fluorescence in situ hybridization (FISH) on formalin‐fixed and paraffin‐embedded (FFPE) tissue sections is currently the gold standard for identification of TFE3 rearrangements. Herein, we report a case of RCC with a morphological appearance of Xp11.2 translocation, and positive TFE3 immunostaining. By FISH, the spots constituting the split signal were barely spaced, suggestive of a chromosome X inversion rather than a translocation. We performed RNA‐seq from FFPE material to test this hypothesis. RNA‐seq suggested a fusion of RBM10 gene exon 17 (Xp11.23) with TFE3 gene exon 5 (Xp11.2). RBM10‐TFE3 fusion transcript was confirmed using specific RT‐PCR. Our work showed that RNA‐Seq is a robust technique to detect fusion transcripts from FFPE material. A RBM10‐TFE3 fusion was previously described in single case of Xp11.2 RCC. Although rare, RBM10‐TFE3 fusion variant (from chromosome X paracentric inversion), therefore, appears to be a recurrent molecular event in Xp11.2 RCCs. RBM10‐TFE3 fusion should be added in the list of screened fusion transcripts in targeted molecular diagnostic multiplex RT‐PCR. © 2016 Wiley Periodicals, Inc.